Multiplicação de Tetrastichus howardi (OLLIFF,1893) (Hymenoptera: Eulophidae) em hospedeiros anternativos - Olive, Emily Lopes (2022)
Tetrastichus howardi (Olliff, 1893) (Hymenoptera: Eulophidae) is a parasitoid of several insect pests in Brazil. However, it is necessary to ensure quality control in the process of successive multiplication on the hosts under laboratory conditions. Thus, the biological and morphological characteristics of T. howardi multiplied in two alternative hosts, Spodoptera frugiperda (J. E. Smith, 1797) (Lepidoptera: Noctuidae) and Tenebrio molitor (Linnaeus, 1758) (Coleoptera: Tenebrionidae) were evaluated. In addition, we identified the parasitoid via molecular taxonomy and determined the metabolic profile of the number of T. howardi descendants from successive multiplications in alternative hosts. In S. frugiperda the parasitoid managed to maintain a higher emergence than in T. molitor, where it tended to decrease the number of offspring until non-emergence after the 10th generation. The cycle length tended to increase in more advanced generations, but the sex ratio was above 60% in both hosts. The length of the tibia and wing did not vary significantly between generations, but parasitoids from pupae of S. frugiperda were larger than those of T. molitor. The obtained DNA sequences had efficiency superior to 99%, through the Barcode of Life Data System. The analysis by gas-chromatography with mass spectometry allowed the quantification of 118 main metabolites of T. howardi. There is potential to use S. frugiperda pupae up to the 19th generation of T. howardi and T. molitor pupae up to the third generation without needing to reinvigorate. The DNA sequences will contribute to the purity of laboratory creations, in addition to providing the molecular database of T. howardi in the neotropical region. The pupae of S. frugiperda and T. molitor are suitable for mass multiplication of T. howardi. However, T. molitor pupae should not be used for more than three successive generations, as there are losses in the quality of the parasitoid.